(untitled) (Eurasian Journal of Philology Science and Education, 2019)
General principles and methods of overcoming the language barrier in teaching English, its components in their relationship and conditionality, focused our attention on a number of requirements, in the process of forming a foreign language communicative ability. At the same time, as is obvious from the discussion in the above paragraph, we did not directly touch on the methodological issues of organizing content in specific training conditions, identifying parts or units in it that are correlated with certain points in the dynamics of the learning process. Meanwhile, the question of determining the main organizational and methodological unit for the organization of the content of teaching English, as methodological sources have shown, has attracted the attention of researchers for many years. The theme is called as such a unit. And we believe that the definition of the methodological status of the topic as the main organizational-substantive unit of instruction, within which the process of activating the cognitive-communicative activity of students is carried out, is currently relevant. Linguistic and linguistic competences are formed indirectly, through the content of educational material and in the process of acquiring communicative competence. The formation of communicative competence is provided by interconnected training in all four types of speech activity based on a communicative and functional approach. At the same time, the need to include communicatively significant speech situations in the training content is rightly emphasized. It is also indicated that the selection of language General principles and methods of overcoming the language barrier in teaching English, its components in their relationship and conditionality, focused our attention on a number of requirements, in the process of forming a foreign language communicative ability. At the same time, as is obvious from the discussion in the above paragraph, we did not directly touch on the methodological issues of organizing content in specific training conditions, identifying parts or units in it that are correlated with certain points in the dynamics of the learning process. Meanwhile, the question of determining the main organizational and methodological unit for the organization of the content of teaching English, as methodological sources have shown, has attracted the attention of researchers for many years. The theme is called as such a unit. And we believe that the definition of the methodological status of the topic as the main organizational-substantive unit of instruction, within which the process of activating the cognitive-communicative activity of students is carried out, is currently relevant. Linguistic and linguistic competences are formed indirectly, through the content of educational material and in the process of acquiring communicative competence. The formation of communicative competence is provided by interconnected training in all four types of speech activity based on a communicative and functional approach. At the same time, the need to include communicatively significant speech situations in the training content is rightly emphasized. It is also indicated that the selection of language